L-Asparaginase Associated Toxicities In Children With Acute Lymphoblastic Leukemia: A Single-center Prospective Cohort Study (Bangladesh Journal of Medicine, 2025)
Background: Acute lymphoblastic leukemia (ALL) is the most common malignancy in children. Asparaginase has played a crucial role in improving the long-term survival. However, the administration of these agents may lead to multifactorial toxicities.So; the objective of this study is to identify the L- asparaginaseassociated toxicity in children with ALL. Methods: This Prospective cohort study was conducted from May 2023 to April 2025 in the Department of Pediatric Hematology and Oncology, Sir Salimullah Medical College Mitford Hospital, Dhaka. A total of 71 children diagnosed with ALL were included in this study. Results Patients aged ³10 years, WBC count at diagnosis ³50,000 × 10y /L, receiving Regimen B, body surface area (BSA)>1m² showed increased risk of toxicity in bivariate analysis. In multivariate analysis there was no significantassociation. Hyperglycemia was the commonest adverse reaction followed by hepatic transaminitis and elevated INR. Less frequent reactions included pancreatitis, hyperbilirubinemia, hypersensitivity and hypofibrinogenemia. Conclusion: Hyperglycemia was the commonest toxicities of L-asparaginase in children of more than 10 years, followed by hepatic transaminitis and elevated INR. The less frequent toxicities included pancreatitis, hyperbilirubinemia, hypersensitivity and hypofibrinogenemia.Bangladesh J Medicine 2025; 36(3): 109-115